Acquisition of genomic events leading to lymphoblastic transformation in a rare case of myeloproliferative neoplasm with BCR–JAK2 fusion transcript. (26th March 2016) - Duployez, Nicolas; Nibourel, Olivier; Ducourneau, Benoît; Grardel, Nathalie; Boyer, Thomas; Bories, Claire; Darre, Stéphane; Coiteux, Valérie; Berthon, Céline; Preudhomme, Claude; Roche‐Lestienne, Catherine
Abstract: We report a case of myeloproliferative neoplasm (MPN) with an atypical t(9;22;15)(p24;q11;q21) translocation, leading to a BCR–JAK2 fusion, associated with a trisomy of chromosome 8 in clonal evolution at karyotype. Patient's evolution was marked by an aggressive clinical course with rapid progression to blast phase within the first year after diagnosis. Examination of matched chronic phase and blast crisis samples by SNP‐array karyotyping identified secondary acquired cryptic genetic events at the time of lymphoblastic transformation, including biallelic IKZF1 alteration and EBF1 and CDKN2A/B codeletions. This case is the first report describing acquisition of secondary genetic events leading to acute lymphoblastic progression in a rare MPN with BCR–JAK2 fusion.